UJI AKTIVITAS LARVASIDA NYAMUK Aedes aegypti DARI BEBERAPA EKSTRAK ASCIDIAN - Moerid, M. Subhan; Mangindaan, Remy E. P.; Losung, Fitje (Sam Ratulangi University, 2013)
Dengue Hemorrhagic Fever (DHF) is a disease caused by virus through Aedesaegypti mosquitoes as the vector. The disease is spreading across the world andendanger and threaten human life. Measures in controlling the vector using the commonlarvaside â€œabateâ€ are in adequate and less affective. The objectives of the research is tofind out larvaside extracted from three kinds of ascidian. The each ascidians (Polycarpaaurata, Didemnum molle and Rophalaea crassa) were extracted with ethanol, and thecrude extracts were subjected to larvasidal test by dissolving in water containing thelarvae. The remarkable extract activity was partition in ethyl acetate, hexane andbuthanol. The results show that extract of Polycarpa aurata has the highest activity. Theactivity of fractions show that ethyl acetate at 100 ppm reveals the highest mortality oflarvae 100% in 8 hours, followed by hexane fraction (12 hours) then buthanol fraction (18hours). All the fractions (Ethyl acetate, Hexane and Buthanol) could totality kill the larvaewithin 24 hours which is comparable to the abate.